Nonspecific ST-Segment and T-Wave (NS-STT) on Electrocardiogram is Associated with Increasing the Incidence of Perioperative Deep Vein Thrombosis in Patients with Lower Extremity Fracture Under 75 Years Old - Ren C (Dove Medical Press, 2021)
Cheng Ren,* Ming Li,* Teng Ma, Yi-Bo Xu, Zhong Li, Han-Zhong Xue, Qian Wang, Yao Lu, Liang Sun, Kun Zhang Department of Orthopedic Trauma, Honghui Hospital, Xi’an Jiaotong University, Xi’an, Shaanxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kun ZhangDepartment of Orthopedic Trauma, Honghui Hospital, Xi’an Jiaotong University, Xi’an, Shaanxi Province, People’s Republic of ChinaEmail hhzhangkun@163.comObjective: This study aims to explore the clinical correlation between nonspecific ST-segment or T-wave (NS-STT) changes and perioperative deep vein thrombosis (DVT) in patients with lower extremity fractures.Methods: One thousand four hundred sixty-nine consecutive patients who suffered lower extremity fractures were screened at Xi’an Honghui Hospital between Feb 2016 and Nov 2018. According to the included and excluded criteria, the patients were included in this retrospective study. After collecting the electrocardiogram baseline, the patients were divided into the NS-STT group and the non-NS-STT group. After comparing the demographic and clinical characteristics, multivariate logistic regression models were used to identify the role of NS-STT changes on perioperative DVT. All analyses were performed with R and EmpowerStats software.Results: Nine hundred and sixty-eight patients were included in the study. Ninety-seven patients (10.02%) had NS-STT changes on the electrocardiogram at admission. A total of 303 patients (31.30%) developed perioperative DVT in lower extremities. The univariate analysis showed that NS-STT segment changes were correlated with perioperative DVT significantly (OR = 3.45, 95% CI: 2.25– 5.30, P < 0.0001). In addition, age ≥ 50 (P < 0.0001), female (OR = 1.50, 95% CI: 1.14– 1.97, P = 0.0038), hypertension (OR = 1.54, 95% CI: 1.08– 2.20, P = 0.0161), blood transfusion (OR = 1.78, 95% CI: 1.34– 2.37, P < 0.0001), joint prosthesis (OR = 3.26, 95% CI: 2.21– 4.81, P < 0.0001), and blood loss ≥ 300 mL (OR = 2.12, 95% CI: 1.50– 3.01, P < 0.0001) were associated with perioperative DVT in lower extremities. We identified the confounding factors of age, gender, classification of internal implants, operation time, blood loss, and infusion. After adjustment for potential confounding factors, NS-STT changes were associated with perioperative DVT (OR = 2.13, 95% CI: 1.33– 3.42; P = 0.0017). The sensitive analysis showed that the result was stable.Conclusion: The NS-STT changes on electrocardiograms are associated with an increase in the incidence of perioperative DVT by 2.13-fold in patients with lower extremity fractures under 75 years old. In clinical practice, surgeons should pay more attention to these patients.Keywords: nonspecific ST-segment and T-wave, NS-STT, electrocardiogram, DVT, lower extremity fracture, logistic regression